Student Management Strategies in Improving the Quality of Tahfidz Learning at Al-Quran Islamic Senior High School Darul Ma’arif North Labuhanbatu - Zuhri Injana; Yusuf Hadijaya; Toni Nasution (Indonesian Technology and Education Journal, 2026)
This study aims to analyze student management in improving the quality of Tahfizh learning at Madrasah Aliyah Al-Qur’an Pondok Pesantren Darul Ma’arif, North Labuhanbatu. The research employs a qualitative approach with a descriptive case study design to examine the processes of planning, implementation, and evaluation of student management in the Tahfizh program. Data were collected through interviews, observations, and documentation involving 15 participants, consisting of one madrasah principal, five Tahfizh teachers, and nine students. The findings indicate that student management is implemented through structured processes that include student recruitment, organized learning activities, and continuous evaluation. Recruitment is conducted using clear selection criteria to ensure students’ initial readiness. The implementation of learning takes place through disciplined routines, including memorization and revision activities under teacher supervision. Evaluation is carried out regularly to monitor students’ progress in memorization and learning consistency. This study highlights that the effectiveness of Tahfizh learning is closely related to the integration of planning, implementation, and evaluation within a structured management system. Rather than focusing solely on instructional techniques, the findings suggest that consistent management practices and supportive learning environments contribute to sustaining students’ memorization progress. The study contributes to providing a contextual understanding of how student management operates in a pesantren setting, particularly in supporting the quality of Tahfizh learning.